The Expected (Signaling) Value of Higher Education - Laura Ehrmantraut; Pia Pinger; Renske Stans (Institute of Labor Economics (IZA), 2020)
This paper explores students' expectations about the returns to completing higher education and provides first evidence on perceived signaling and human capital effects. We elicit counterfactual labor market expectations for the hypothetical scenarios of leaving university with or without a degree certificate among a large and diverse sample of students at different stages of higher education. Our findings indicate substantial perceived returns to higher education. Moreover, by exploiting within-individual variation, we document sizeable expected labor market returns from signaling, whereas perceived productivity-enhancing (human capital) returns seem to be less pronounced. Over the expected course of career, we find lasting education premia as well as evidence consistent with employer learning.
Keywords: I21; I23; I26; J24; J31; J32; J44; 330; signaling; returns to education; higher education; educational attainment; licensing